Pharmaceutical polymorphism of a 5´-O-oxalatoyl prodrug of zidovudine (azidothymidine) - Diego E. Kassuha, Flavia P. Bruno, Gustavo A. Monti, Norma R. Sperandeo (Journal of Applied Pharmaceutical Science, 2020)
The importance of polymorphism in pharmaceuticals makes its study relevant. The aim of this study was to investigate the solid-state forms in which 3´-azido-2´, 3´-dideoxi-5´-O-oxalatoyl-thymidinic acid (AZT-Ac), a zidovudine (AZT) prodrug with improved pharmacokinetic properties, may exist. Samples were prepared using different crystallization conditions and characterized using powder X-ray diffraction, solid-state nuclear magnetic resonance, differential scanning calorimetry, thermogravimetry, and hot-stage microscopy. Pharmaceutical relevant properties such as solid-state stability and intrinsic dissolution rate (IDR) at 37°C in simulated gastric fluid (SGF) were also evaluated. AZT-Ac was found to able to exist as a crystalline polymorph (AZT-Ac-C) and an amorphous phase (AZT-Ac-A), which were thoroughly characterized. At 40°C/75% relative humidity (RH), AZT-Ac-A, in part, devitrified to AZT-Ac-C and partially hydrolyzed to AZT after 7 and 14 days of storage, respectively. AZT-Ac-C was physically stable at 40°C/75% RH but partly hydrolyzed to AZT after 14 days of storage. In SGF, AZT-Ac-C exhibited a linear ID profile and provided an ID rate of 0.494 mg/min/cm2, whereas AZT-Ac-A exhibited a nonlinear profile. Therefore, the crystalline form demonstrated the advantages over the amorphous one in terms of solid-state stability and IDR, but the approaches to enhance its stability should be considered for further formulation of this prodrug.
Keywords: Crystallization, differential scanning calorimetry, drugs, nuclear magnetic resonance, nucleoside inhibitors, X-ray diffraction.